GARAP TARI KETHEK OGLENG DI DESA NGAMBARSARI, KARANGTENGAH KABUPATEN WONOGIRI - Nurpilang, Eka; Subagya, Hadi (Greget: Jurnal Kreativitas dan Studi Tari, 2021)
This article is the result of research from ideas to reveal the creativity of the Kethek Ogleng Dance in Ngambarsari village, Karangtengah sub-district, Wonogiri district, namely the Bawang Sari Cultural Community (BBS) with reference to the artistry of community leaders. The problem that was revealed was working on the Kethek ogleng dance in N Gambarsari village, Karangtengah sub-district, Wonogiri district. This research is qualitative in nature with data collection strategies through observation, interviews, and literature studies. The form theory uses Suzane K Langer's statement which is supported by Soemandyo Hadi's concept of form and the main concept of "Garap" uses Rahayu Supanggah's theory. The concept of this form is used to see the form of the Kethek Ogleng dance and the concept of Garap is used to see the work on the Kethek Ogleng dance obtained from the village of Ngambarsari, especially in the Bawang Sari Cultural community. The results of this study state that the Kethek Ogleng dance is the result of a planned work by thinking about the original dance of Kethek Ogleng and then combining it with the Surakarta style. This Bawang Sari culture works on the structure of the movement that appears, so that it becomes a kethek ogleng dance according to its own characteristics.Keywords: shape, Kethek Ogleng, Wonogiri.